Establishing Validity for Measures of Executive Functioning and Behavior in Children and Adolescents with Sickle Cell Disease - Purvis, Lee Nathaniel (East Carolina University, 2013)
This study examined the criterion validity of the Behavior Rating Inventory for Executive Functioning (BRIEF; Gioia, Isquith, Guy, & Kenworthy, 2000) and the Behavior Assessment System for Children, 2nd Edition (BASC-2; Reynold & Kamphaus, 2004) for children and adolescents with sickle cell disease (SCD) in a clinically referred pediatric SCD population. It was predicted that criterion validity would be supported for the BRIEF and BASC-2 as evidenced by the participants from the clinically referred sample having elevated levels of executive dysfunction on the BRIEF's Behavior Regulation Index and Metacognitive Index as compared to the normative sample of the BRIEF, and elevated levels of behavioral and emotional problems and lowered adaptive functioning on the BASC-2's internalizing, externalizing, and adaptive domains as compared to the normative sample of the BASC-2. It was also predicted that criterion validity would be supported for the BRIEF and BASC-2 as evidenced by the participants from the clinically referred sample with SCD and stroke evidencing more executive dysfunction and behavioral problems as compared to those with SCD and without stroke. Comparisons of mean scores were made between pediatric SCD patients and the criterion T-score of 50 and between pediatric SCD patients with and without stroke. The percentage of participants' ratings in the at-risk and clinical ranges on the BRIEF and BASC-2 were compared to 16%, which is the standard percentage of the normative sample within these classifications and they were also compared to the percentage of participants with SCD and without stroke. Results from t-test analyses indicated that the mean of the participants' T-scores on the BRI and MI of the BRIEF and externalizing, internalizing, and adaptive scales BASC-2 were significantly different than the criterion T-score of 50 in every comparison. No significant differences were found with regards to stroke status. Results from chi-square analyses indicated a higher percent of participants with SCD fell in the at-risk and clinical ranges on the BRIEF and BASC-2 when compared to 16% in every comparison but not in regards to stroke status. These results suggest that the BRIEF and BASC-2 can detect deficits in executive functioning and behavior among children and adolescents with sickle cell disease but more research is needed to determine if these measures can detect differences between participants with SCD with and without stroke.
Keywords: Psychology; Behavioral sciences; Clinical psychology; BASC-2; BRIEF; Criterion validity; Executive functioning; Pediatric; Sickle cell disease; Sickle cell anemia in children; Sickle cell anemia in adolescence; Executive functions (Neuropsychology); Behavioral assessment of children; Behavior Assessment System for Children